Race/ethnicity and untreated dental caries: the impact of material and behavioral factors - Reid BC, Hyman JJ, Macek MD. (Blackwell Synergy, 2004)
To use nationally representative data, group variables into categories of material and behavioral factors, and assess their relative contribution to racial/ethnic variation in untreated caries.